Проблемы русско-монгольских связей конца XIX начала XX вв. в исследованиях Е.М.Даревской (Journal of International Studies, 2013)
English title: Mutual Relations of Russia and Mongolia in the end of XIX and Beginning of XX Century in Research Works of Darevskaya E.M